Analisis Fenomenologis Pada Persepsi Siswa Tentang Pembelajaran Bahasa Arab Melalui Model Pembelajaran Kooperatif Di MAN Kota Magelang - Asep Sunarko; Arini Lutfi Solihah; Muflikhatul Munawwaroh (DAS Institute, 2025)
This study aims to analyze the application of cooperative learning model in Arabic language learning at MAN Kota Magelang, as well as to understand students' perceptions of the model. The importance of this discussion lies in the role of Arabic as a language that is not only used in daily communication, but also as a profound language of religion and literature. Effective Arabic learning can be achieved by using appropriate methods, such as cooperative learning models, which encourage students' active involvement. The research method used is a qualitative approach with a field study. The data collection technique was conducted through observation and in-depth interviews with the 11th grade students of MAN Kota Magelang. The collected data were analyzed using the Miles and Huberman analysis model, which includes data reduction, data presentation, and conclusion drawing. The results showed that the application of cooperative learning model in Arabic class had a positive impact on students' understanding of the material. This model increases social interaction between students, accelerates task completion, and encourages cohesiveness in the group. Students also revealed that they preferred learning with different gender group members, which increased diversity of opinions and cooperation. In general, the cooperative learning model is proven effective in improving Arabic learning outcomes at MAN Kota Magelang.